Risk of rubella in pregnancy - Kanra, Güler (The Turkish Journal of Pediatrics, 1982)
Rubella should not be diagnosed solely on the basis of clinical findings. The diagnosis must be confirmed by serological and virological studies in all pregnant women who come into contact with the infection. Therapeutic abortion should be recommended only if acute primary infection has been confirmed by these tests.
Keywords: intrauterine infection; rubella; therapeutic abortion